2020
DOI: 10.1210/clinem/dgaa158
|View full text |Cite
|
Sign up to set email alerts
|

Short-term High-fat Overfeeding Does Not Induce NF-κB Inflammatory Signaling in Subcutaneous White Adipose Tissue

Abstract: Context It is unclear how white adipose tissue (WAT) inflammatory signaling proteins respond during the early stages of overnutrition. Objective To investigate the effect of short-term, high-fat overfeeding on fasting abdominal subcutaneous WAT total content and phosphorylation of proteins involved in nuclear factor-κB (NF-κB) inflammatory signaling, systemic metabolic and inflammatory biomarkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In addition, many new findings in mice and humans suggest that JNK activation might induce insulin resistance and lead to obesity [ 47 , 48 ]. Meanwhile, NF-κB inflammatory regulation signaling pathway is up-regulated in the brain tissue of 14weeks or 16weeks HFD-feeding mice [ 20 , 49 ] as well NF-κB inflammatory signaling is unchanged in subcutaneous white adipose tissue after short-term high-fat overfeeding [ 16 ]. On the other hand, our results showed that after 7 days or 21 days consumption of HFD led to a significant decrease in phospho-NF-κB p65 and phospho-JNK simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many new findings in mice and humans suggest that JNK activation might induce insulin resistance and lead to obesity [ 47 , 48 ]. Meanwhile, NF-κB inflammatory regulation signaling pathway is up-regulated in the brain tissue of 14weeks or 16weeks HFD-feeding mice [ 20 , 49 ] as well NF-κB inflammatory signaling is unchanged in subcutaneous white adipose tissue after short-term high-fat overfeeding [ 16 ]. On the other hand, our results showed that after 7 days or 21 days consumption of HFD led to a significant decrease in phospho-NF-κB p65 and phospho-JNK simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even as little as 3–10 days exposure, short-term HFD consumption has demonstrated that production of proinflammatory cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNFα), apoptosis and memory impairments in humans and rodents in long before obesity symptoms appearance [ 11 15 ]. Nevertheless, a literature suggests that short-term HFD overnutrition does not induce NF-κB inflammatory signaling of subcutaneous white adipose tissue in humans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%